THE EFFECT OF JEMBER FASHION CARNAVAL AND SPONSORSHIP ON COMPANY IMAGE PT. MARTINA BERTO - Vegys Virgynitha Yussy Jessyca Gultom; Angela Clarissa; Marcha Chryztantya (Universitas Prof. Dr. Moestopo (Beragama), 2019)
In 2015, Indonesia's GDP growth reached 852.24 trillion and fashion became an export commodity that dominated up to 56%. This stimulates the emergence of various fashion shows in Indonesia, one of which is the Jember Fashion Carnaval event sponsored by PT. Martina Berto from 2003. This study aims to find out whether there is an international standard JFC event that can improve the company's image of PT. Martin Berto as a local cosmetics company with international standard. This study uses a quantitative methodology with an instrument test in the form of a questionnaire distributed online to 100 respondents. The results of the study show that JFC events and sponsorships contribute to the corporate image of PT. Martina Berto at 53.6%. Separately, the event variable has an effect of 0.614 and the sponsorship variable has an effect of 0.326 on the corporate image of PT. Martina Berto. The results of this study can be used to increase the variable-forming elements that affect the company's image.